A 12-week lifestyle intervention: effects on fatigue, fear, and nutritional status in children with a Fontan circulation - Scheffers, L. E.; Helbing, W. A.; Pereira, T.; Walet, S.; Utens, E. M. W. J.; Dulfer, K.; van den Berg, L. E. (Frontiers in Pediatrics, 2023)
Introduction: Children and adolescents with a Fontan circulation are less physically active compared to healthy peers. In the current study, effects of a 12-week lifestyle intervention on fatigue, fears regarding exercise, caloric intake, rest energy expenditure (REE) and body composition were measured in children with a Fontan circulation.Methods: This study was a semi-cross over randomized controlled trial. The lifestyle intervention consisted of a 12 weeks high-weight resistance training (3 supervised training sessions a week) supported by high-protein diet (>2 grams/kilogram) and tailored recommended caloric intake. Fatigue (measured by the validated PedsQol Multi fatigue scale), fears regarding exercise (measured on a fear thermometer), REE (measured using indirect calorimetry), caloric intake and body composition using air displacement plethysmography and four-skinfold method were measured before and after the intervention and control period.